Potential of Gracilaria tenuistipitata var. liui grown in Nuniachara, Cox’s Bazar, Bangladesh (Bangladesh Journal of Scientific and Industrial Research, 2021)
During selection of Gracilaria tenuistipitata var. liui (red seaweed) growing naturally at Nuniachara sand-flat south-east of Moheshkhali channel, Cox’s Bazar local fishermen informed that Rakhaine and Chakma tribes of Cox’s Bazar and Bandarbon consume the seaweed. To ascertain the quality of the organism as “Seafood” analysis of its nutritional status was carried out using three replicates in many cases. Percentage composition of total crude protein, crude fiber, crude lipid, carbohydrates, ash and moisture were 25.55 ± 0.18, 5.65 ± 0.13, 0.16 ± 0.03, 45.93 ± 1.53, 10.61 ± 0.69 and 12.10 ± 0.25%, respectively. Mineral contents such as phosphorus, calcium, magnesium, iron and copper were 596.90 ± 10.4, 132.75 ± 3.4, 3.90 ± 1.2, 80.13 ± 2.45 and3.99 ± 1.2mg/100gdry wt., respectively. Heavy metals such as Pb, As, Cr and Cd were 0.031, 0.01, 0.06 and 0.02 mg/kg dry wt. respectively, which are below tolerance level. The seaweed contained 9.03% nine essential amino acids and 7.52% five non-essential amino acids. The quantity of total energy, β-carotene and vitamin C were 294.56 Kcal/100g, 11.54 ± 1.20 and 2.5 mg/100g, respectively. Presence of high crude protein, amino acid profiles, β-carotene, phosphorus and low crude lipid and heavy metals made Gracilaria tenuistipitata var. liui to be considered as a good human food supplement.Bangladesh J. Sci. Ind. Res.56(1), 39-46, 2021